Productivity enhancements of compound parabolic concentrator tubular solar stills - Thirugnanasambantham, Arunkumar; Velraj, Ramalingam; Denkenberger, David C.; Sathyamurthy, Ravishankar; Kumar, K. Vinoth; Ahsan, Amimul (Elsevier, 2016)
The performance of compound parabolic concentrator assisted tubular solar still (CPC-TSS) and compound parabolic concentrator-concentric tubular solar still (CPC-CTSS) (to allow cooling water) with different augmentation systems were studied. A rectangular saline water trough of dimension 2 m × 0.03 m × 0.025 m was designed and fabricated. The effective collector area of the still is 2 m × 1 m with five sets of tubular still – CPC collectors placed horizontally with north-south orientation. Hot water taken from the CPC-CTSS was integrated to a pyramid type and single slope solar still. Diurnal variations of water temperature, air temperature, cover temperature and distillate yield were recorded. The results showed that, the productivity of the un-augmented CPC-TSS and CPC-CTSS were 3710 ml/day and 4960 ml/day, respectively. With the heat extraction technique, the productivity of CPC-CTSS with a single slope solar still and CPC-CTSS with a pyramid solar still were found as 6460 ml/day and 7770 ml/day, respectively. The process integration with different systems cost was found slightly higher but the overall efficiency and the produced distilled water yield was found augmented.